2009
DOI: 10.1177/0040517507090504
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis of Tensile load — Strain Route of Knitted Fabrics under Extension and Recovery Processes Estimated by Strain History

Abstract: Hysteresis phenomenon of tensile load (stress) under extension and recovery processes were estimated in terms of time dependence of tensile load by using several kinds of knitted fabrics. The measurements were done under strip biaxial extension corresponding to uniaxial extension with a fixed dimension in the direction perpendicular to elongation. The present concept was based on tensile load (stress) relaxation in elongation and restricted sides. To attempt mathematical evaluation, a simple hypothesis describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Due to microstructural deformation and fiber slippage, the knitted fabric is a type of viscoelastic material, which usually shows a time-dependent elastic behavior leading to a viscoelasticity. 39 A cyclic axial tensile testing method 40 was used to measure the mechanical property of the WMF for testing the viscoelasticity, and the unloading strain was used to evaluate the hysteresis effect of the auxetic structure. The fabric samples were cut into 50 mm  80 mm rectangular shapes; 30 mm out of the 80 mm length was for fixing the samples on the MTS, and therefore the actual testing area was 50 mm  50 mm, conditioned for 24 hours at 25 AE 1 C and 65% humidity before mechanical experiment and Poisson's ratio measurement.…”
Section: Mechanical Experimentsmentioning
confidence: 99%
“…Due to microstructural deformation and fiber slippage, the knitted fabric is a type of viscoelastic material, which usually shows a time-dependent elastic behavior leading to a viscoelasticity. 39 A cyclic axial tensile testing method 40 was used to measure the mechanical property of the WMF for testing the viscoelasticity, and the unloading strain was used to evaluate the hysteresis effect of the auxetic structure. The fabric samples were cut into 50 mm  80 mm rectangular shapes; 30 mm out of the 80 mm length was for fixing the samples on the MTS, and therefore the actual testing area was 50 mm  50 mm, conditioned for 24 hours at 25 AE 1 C and 65% humidity before mechanical experiment and Poisson's ratio measurement.…”
Section: Mechanical Experimentsmentioning
confidence: 99%
“…To pursue the more detailed analysis, the relationship between tensile load and pressure under extension and recovery processes was analyzed in terms of the hysteresis phenomenon based on the concept that the drastic decrease of tensile load is attributed to the tensile load (stress) relaxation mode [12]. If the strain is due to time dependence described as a summation of step functions concerning strain history, tensile load (stress) under extension process can be represented by using hereditary integral according to the Boltzmann superposition principle.…”
Section: Tion the Comparison Between Specimens A And C Indicated That Considerable Hysteresis Effect On Tensile Load Along The Extension mentioning
confidence: 99%
“…In equation (6), A, B, α and β are the coefficient to represent time dependence of strain against the external applied tension [12]. They are given by (7) As discussed in our previous paper [13], equation (7) representing two relaxation modes is only a formula to represent tensile load (stress), but the origin of actual time dependence is obviously attributed to a number of unknown factors such as plastic deformation, slippage and Figure 7 Tensile load (on left hand) and pressure (on right hand) against strain under extended and recovery processes measured for specimen A.…”
Section: Tion the Comparison Between Specimens A And C Indicated That Considerable Hysteresis Effect On Tensile Load Along The Extension mentioning
confidence: 99%
See 1 more Smart Citation
“…Popper (1966) assessed the role of friction in the biaxial behaviour of knitted fabrics through a theoretical analysis and demonstrated that its effect is very important even if the value of the coefficient of kinetic friction is low (0.1). This effect being opposed to the sliding direction, its contribution acts inversely during loading and unloading steps, leading to a very pronounced hysteretic behaviour of knitted fabrics under biaxial (Popper, 1966) and uniaxial (Matsuo and Yamada, 2009) tension. The sensitivity to friction is exacerbated by the exponential form of the drive belt formula that may apply at the loops crossing points due to yarn curvature (Popper, 1966).…”
Section: Introductionmentioning
confidence: 99%